Dental caries experience in high risk soft drinks factory workers of South India: A comparative study - Sandeep Kumar; Shashidhar Acharya; Ramprasad Vasthare; Siddharth Kumar Singh; Anjali Gupta; Nitai Debnath (Wolters Kluwer Medknow Publications, 2014)
Background: The consumption of soft-drinks has been associated with dental caries development. Objective: The aim was to evaluate dental caries experience amongst the workers working in soft-drink industries located in South India and compare it with other factory workers. To evaluate the validity of specific caries index (SCI), which is newer index for caries diagnosis. Materials and Methods: This was a cross-sectional study carried out among 420 workers (210 in soft-drinks factory and 210 in other factories), in the age group of 20-45 years of Udupi district, Karnataka, India. Index used for clinical examination was decayed, missing, filled surfaces (DMFS) index and SCI. Results: The mean and standard deviation (SD) of decayed surface (5.8 ± 1.8), missing surface (4.3 ± 2) and filled surface (1.94 ± 1.95) and total DMFS score (12.11 ± 3.8) in soft-drinks factory workers were found to be significantly higher than the other factory workers. The total SCI score (mean and SD) was found to be significantly higher in soft-drinks factory workers (5.83 ± 1.80) compared with other factory workers (4.56 ± 1.45). There was a high correlation obtained between SCI score and DMFS score. The regression equation given by DMFS = 1.178 + 1.866 (SCI scores). Conclusion: The caries experience was higher in workers working in soft-drinks factory and this study also showed that specific caries index can be used as a valid index for assessing dental caries experience.